2017
DOI: 10.3390/cli5010005
|View full text |Cite
|
Sign up to set email alerts
|

Hydroclimatic Characteristics of the 2012–2015 California Drought from an Operational Perspective

Abstract: California experienced an extraordinary drought from 2012-2015 (which continues into 2016). This study, from an operational perspective, reviewed the development of this drought in a hydroclimatic framework and examined its characteristics at different temporal and spatial scales. Observed and reconstructed operational hydrologic indices and variables widely used in water resources planning and management at statewide and (hydrologic) regional scales were employed for this purpose. Parsimonious metrics typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…In addition to annual precipitation and temperature, wet season precipitation and seasonal temperature were also applied as important indices in planning studies [45]. Wet season precipitation accounts for a majority portion of the annual precipitation.…”
Section: Difference From the Baselinementioning
confidence: 99%
See 2 more Smart Citations
“…In addition to annual precipitation and temperature, wet season precipitation and seasonal temperature were also applied as important indices in planning studies [45]. Wet season precipitation accounts for a majority portion of the annual precipitation.…”
Section: Difference From the Baselinementioning
confidence: 99%
“…This is particularly true in a warming climate for dry regions where evapotranspiration is an important component of the water budget. For instance, the most recent 2012-2015 California drought was a typical "warm drought" characterized by record-low precipitation and snowpack as well as record-high temperature [45,[53][54][55]. As a result, SPI may not be the most appropriate index for drought analysis in California which contains many arid or semi-arid areas.…”
Section: Drought Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Total accumulated PRISM precipitation during the study period demonstrates the characteristic pattern of orographic enhancement over the western United States (Dettinger et al, ; Roe, ), indicated by steep precipitation gradients across the Coast Ranges, Cascade Mountains, and Sierra Nevada Mountains (Figure a). Additionally, there is a climatological north‐south precipitation gradient (Daly et al, ) that was particularly pronounced over the study period due to below average precipitation in California during the 2014/2015 and 2015/2016 winter seasons (He et al, ). Figure b demonstrates the ability of GPM‐DPR to reproduce PRISM's salient precipitation patterns.…”
Section: Gpm‐dpr In Situ Validationmentioning
confidence: 99%
“…A year having fewer or greater than average of such events can be particularly dry or wet. The State is thus prone to hydroclimatic extremes, with the most recent examples being water year 2015 (record high temperature and record low snowpack observed across the State) [20] and water year 2017 (record high precipitation in the Northern Sierra). Any changes to precipitation, temperature and runoff events, particularly extremes, could have long-lasting adverse impacts on the society, economy, and environment of the State.…”
Section: Introductionmentioning
confidence: 99%